Rare diseases of bone: Erdheim-Chester and Rosai-Dorfman non-Langerhans cell histiocytoses. Issue 6 (23rd June 2018) - Mavrogenis, Andreas F.; Igoumenou, Vasilios G.; Antoniadou, Thekla; Megaloikonomos, Panayiotis D.; Agrogiannis, George; Foukas, Periklis; Papageorgiou, Sotirios G.
Abstract : Non-Langerhans cell histiocytosis (N-LCH) summarizes a group of rare diseases with different clinical presentations, pathogenesis and morphology. These include primary cutaneous N-LCH, cutaneous N-LCH with systemic involvement, and primary extracutaneous systemic forms with occasional cutaneous involvement. The juvenile (JXG) and non-juvenile xanthogranuloma (N-JXG) family of histiocytoses are N-LCH: the JXG family consisting of the JXG (cutaneous), xanthoma disseminatum (cutaneous and systemic) and Erdheim-Chester disease (ECD; systemic); and the N-JXG family consisting of the solitary reticulohistiocytoma (cutaneous), multicentric reticulohistiocytosis (cutaneous and systemic) and Rosai-Dorfman disease (RDD; systemic). ECD is a clonal disorder from the JXG family of N-LCH; RDD is a reactive proliferative entity from the non-juvenile xanthogranuloma family of N-LCH. ECD and RDD N-LCH are rare disorders, which are difficult to diagnose, with multi-organ involvement including bone and systemic symptoms, and which respond to therapy in an unpredictable way. The key to successful therapy is accurate identification at tissue level and appropriate staging. Patients should be observed and monitored in a long-term pattern. Prognosis depends on disease extent and the organs involved; it is generally good for RDD disease and variable for ECD. Cite this article: EFORT Open Rev 2018;3:381-390. DOI: 10.1302/2058-5241.3.170047